THE ROLE OF ZISWAF IN ENSURING THE RESILIENCE OF MSMES DURING THE COVIDͳ19 PANDEMIC IN INDONESIA - Ishmah Zahirah; Laila Pimada Masruro; Muhammad Fakhri Arsyi; Irvan Fauzi (Imara: JURNAL RISET EKONOMI ISLAM, 2022)
The study aims to identify the contribution of ZISWAF to the availability of capital, management, and marketing of MSMEs’ products. This study also looks at the development and role of ZISWAF and MSMEs during the COVID-19 pandemic in Indonesia. Indeed, the COVID-19 pandemic has affected the economic condition due to the implementation of large-scale social restrictions. This study used a qualitative approach with the library method. This study used secondary data taken from relevant research results, books, articles, and scientiϔic works. The result showed that ZISWAF contributed to ensuring the resilience of MSMEs through their diverse ϔinancial and giveaway programs.